Historical and contemporary management of infantile hemangiomas: a single-center experience - Zou, Yun; Wu, Zhiping; Jin, Pingliang; Fu, Ronghua; Cheng, Jun; Bai, Hanxiang; Huang, Mengyu; Huang, Xiangqun; Yuan, Hua (Frontiers in Pharmacology, 2024)
Objective: This study explores the 22-year evolution of Infantile Hemangiomas (IHs) treatment strategies at a single-center hospital, aiming to establish an individualized IHs management protocol. Methods: Retrospective review of IHs infants 2000-2022 at the Department of Plastic Surgery, Jiangxi Provincial Children's Hospital. Results: In our study of 27,513 IHs cases, 72.2% were female, with the median age at first hospital visit being 25 days. The majority of cases had localized and superficial lesions primarily on the head, face, and neck (67.5%). Ulceration rates fell from 21.1% to 12.6% with the introduction of propranolol. Management strategies have shifted over time, with the proportion of cases undergoing expectant management dropping from 32.9% to 12.4%. Since 2008, 26.1% of patients were treated with oral propranolol, largely replacing corticosteroids. Topical β-blockers have been used in 12.1% of cases, leading to a reduction in local injection therapy from 20.8% to 13.2%. Laser therapy, introduced in 2016, has been used in 13.8% of cases, while surgical excision has dropped from 25.0% to 8.5% due to alternative treatment options. Combination therapy was used in 8.8% of cases post-2015, indicating a rising trend. Drawing from the evolution of IHs management strategies, an individualized protocol for the management of IHs was successfully established. Conclusions: Treatment for IHs has evolved over recent decades, with less invasive medical interventions increasingly replacing more invasive methods. Furthermore, a personalized treatment protocol established in this study could boost the cure rate of IHs while minimizing potential side effects and complications.